Venous Thromboembolism in Brain Tumors: Risk Factors, Molecular Mechanisms, and Clinical Challenges - Riedl, Julia; Ay, Cihan (Seminars in Thrombosis and Hemostasis, 2019)
Venous thromboembolism (VTE) is a common complication in patients with primary brain tumors, with up to 20% of patients per year having a VTE event. Clinical risk factors for VTE include glioblastoma subtype, paresis, or surgery. Furthermore, specific factors playing a role in tumor biology were recently identified to predispose to prothrombotic risk. For instance, mutations in the isocitrate dehydrogenase 1 (IDH1) gene, which occurs in a subgroup of glioma, correlate with risk of VTE, with low incidence in patients with presence of an IDH1 mutation compared with those with IDH1 wild-type status. In addition, expression of the glycoprotein podoplanin on brain tumors was associated with both intratumoral thrombi and high risk of VTE. As podoplanin has the ability to activate platelets, a mechanistic role of podoplanin-mediated platelet activation in VTE development has been suggested. From a clinical point of view, the management of patients with primary brain tumors and VTE is challenging. Anticoagulation is required to treat patients; however, it is associated with increased risk of intracranial hemorrhage. This review focuses on describing the epidemiology, risk factors, and mechanisms of brain tumor-associated thrombosis and discusses clinical challenges in the prevention and treatment of VTE in patients with brain tumors.
Keywords: brain tumors; venous thromboembolism; cancer-associated thrombosis; podoplanin; platelets